Preferensi Memilih Generasi Z Kota Makassar Menghadapi Pemilu 2024 (Journal of Peace, Security and Democracy, 2026)
Generation Z has become a focus of attention in the context of elections because this group is bringing significant changes to the way they participate and interact with socio-political issues through technology. The large number of this generation also demonstrates the potential influence they can have on the democratic process. Furthermore, with easy access to technology and information, Generation Z has the ability to quickly articulate their views through social media. The purpose of this study is to identify and explain the factors that shape Generation Z's voting preferences in the context of elections. The research method used in this study is a descriptive qualitative research method. Data collection was conducted through in-depth interviews with several informants and used two types of data: primary and secondary. The results of this study indicate that several factors shape Generation Z's voting preferences in elections. First, psychological factors due to the strong influence of emotional impulses and rapid exposure to information through social media. Second, rational choice factors, where Generation Z chooses based on the benefits they receive.